Inovasi dan Peran Masyarakat dalam Perlindungan dan Upaya Reintegrasi Purna Anak yang Berkonflik dengan Hukum - Ameylia Puspita Rosa Dyah Ayu Arintyas; Hakimul Ikhwan; Muhadjir Darwin (Research and Development Agency Ministry of Home Affairs, 2026)
This study aims to examine the role of community and innovation in supporting the social reintegration of former children in conflict with the law (CCL) in Yogyakarta. Through case studies and in-depth interviews with children in conflict with the law, correctional officers, and community representatives, the study found that community involvement in the form of peer support groups and mentoring programs plays a crucial role in helping former children rebuild social relationships and overcome stigma. In addition, the use of technology-based applications that connect former children with support services, such as counseling and skills training, has also proven effective. The study further identifies several challenges, such as a lack of inter-agency coordination and limited resources. It suggests the importance of developing more integrated programs that involve the community, government, and private sector to support the social reintegration of former children in conflict with the law.